Pengaruh Pay Satisfaction Terhadap Organizational Citizenship Behavior (OCB) Dimediasi Work Engagement - Arifin, Arifin; Ariffin, Zakhyadi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to test and analyze the effect of Pay Satisfaction on Organizational Citizenship, the effect of Pay Satisfaction on Work Engagement, the effect of Work Engagement on Organizational Citizenship behavior, and the effect of Pay Satisfaction on Organizational Citizenship Behavior through ASN Work Engagement in Pambalah Batung General Hospital. This study used a quantitative method, with a cross-sectional time dimension. the sample in this study was about 159 people. The data analysis used is descriptive analysis and to test the effect of the model on the PLS-based structure. The results showed that there was an effect of Pay Satisfaction on Organizational Citizenship Behavior, there was an effect of Pay Satisfaction on Work Engagement, there was an effect of Work Engagement on Organizational Citizenship Behavior and there was an effect of Pay Satisfaction on Organizational Citizenship Behavior through ASN Work Engagement at Pambalah Hospital Batung. Suggestions to Pambalah Batung General Hospital need to pay attention to employee Pay Satisfaction because Pay Satisfaction has an impact on Organizational Citizenship Behavior through Work Engagement and Work Engagement also has an impact on Organizational Citizenship Behavior. If these variables can be considered, of course they will have an impact on the services to the community provided by the Pambalah Batung Hospital